Estimación de los valores económicos para la producción y caracteres funcionales en el ganado lechero de la asociación Aspranues de la parroquia de Belisario Quevedo para el establecimiento de los objetivos de mejoramiento genético. - Viteri Barrera, Patricia Lizbeth (2021)
The lack of register in the farms, leads to a lack of knowledge of the production cost, and as they do not have production register, it is not possible to establish what our genetic improvement objectives are. By analyzing the production data, it is possible to make decisions that allow to increase the efficiency and profitability of dairy farms. Also, the best cows can be selected based on the established objectives with the ability to transmit those characters to the next generation. Therefore, in the present research project, the dairy production of the Nueva Esperanza Food Production Association (ASPRANUES), located in the Manzanapamba neighborhood, Belisario Quevedo parish, of Latacunga canton was economically analyzed. Which constitutes an associative enterprise made up of 12 women, who have milk production cows and give added value to their primary production by making cheese in an artisanal way, after a process of education and training with the support of different public and private institutions.